Detecting archaeological sites in the eastern Sahara using satellite remote sensing and digital image processing - Corrie, RK (2015)
Advancements in remote sensing instrumentation are providing more detailed surveys of our planet using synoptic observations from a global, regional, and local perspective. This D.Phil. research project proposes novel techniques for detecting archaeological sites in the hyperarid desert regions and moisture-rich coastal areas of the eastern Sahara, by examining multispectral satellite imagery in the optical and microwave (radar) regions of the electromagnetic (EM) spectrum. The methodology uses sensors onboard spaceborne platforms (in contrast to airborne instruments or ground based geophysical survey) – weighted heavily towards an active radar approach. Landsat-7 ETM+, Shuttle Radar Topography Mission (SRTM), and PALSAR represent the principal imagery types used throughout this work.